An acquired factor V inhibitor induced uncontrolled bleeding in a postsurgery patient - Riccardo Bruna; Riccardo Moia; Alessandra Valpreda; Enrico Dosio; Roberta Rolla; Augusto Federici; Umberto Dianzani; Gianluca Gaidano; Andrea Patriarca (Clinical Case Reports, 2021)
Abstract This case report highlights the challenges in controlling bleeding and correcting coagulation tests through the use of bypassing agents in patients with FV inhibitors.